Optimization of poly(l-lactic acid)/segmented polyurethane electrospinning process for the production of bilayered small-diameter nanofibrous tubular structures - Montini Ballarin, Florencia (2014)
The present study is focused on the electrospinning process as a versatile technique to obtain nanofibrous tubular structures for potential applications in vascular tissue engineering. A bilayered scaffolding structure composed of poly(L-lactic acid) (PLLA)/bioresorbable segmented polyurethane (SPEU) blends for small-diameter (5 mm) vascular bypass grafts was obtained by multilayering electrospinning. Polymer blend ratios were chosen to mimic the media and adventitia layers. The influence of the different electrospinning parameters into the fiber formation, fiber morphology and fiber mean diameter for PLLA, SPEU and two PLLA/SPEU blends were studied. Flat and two-parallel plate collectors were used to analyze the effect of the electrostatic field on the PLLA nanofiber alignment in the rotating mandrel. Membrane topography resulted in random or aligned nanofibrous structures depending on the auxiliary collector setup used. Finally, composition, surface hydrophilicity, thermal properties and morphology of nanofibrous scaffolds were characterized and discussed. Since the development of tissue engineered microvascular prostheses is still a challenge, the prepared scaffolding tubular structures are promising candidates for vascular tissue engineering.